Learning Mechanics and Game Mechanics Under the Perspective of Self-Determination Theory to Foster Motivation in Digital Game Based Learning. (February 2017) - Proulx, Jean-Nicolas; Romero, Margarida; Arnab, Sylvester
Background . Using digital games for educational purposes has been associated with higher levels ofmotivation among learners of different educational levels. However, the underlying psychological factors involved indigital game based learning (DGBL ) have been rarely analyzed consideringself-determination theory (SDT ); the relation of SDT with theflow experience has neither been evaluated in the context of DGBL. Aim . This article evaluates DGBL under the perspective of SDT in order to improve the study of motivational factors in DGBL. Results . In this paper, we introduce theLMGM-SDT theoretical framework, where the use of DGBL is analyzed through theLearning Mechanics and Game Mechanics mapping model (LM-GM ) and its relation with the components of the SDT. The implications for the use of DGBL in order to promote learners' motivation are also discussed.